1999
DOI: 10.1518/001872099779610969
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention to Increase Construction Workers' Use of Hearing Protection

Abstract: In this project we tested the effectiveness of a theory-based intervention (video, pamphlets, and guided practice session) to increase the use of hearing protection devices (HPDs) among Midwestern construction workers and a national group of plumber/pipefitter trainers. Posttest measures were collected 10-12 months following this intervention. Pender's Health Promotion Model (1987) provided the conceptual basis for development of the training program. A total of 837 high-noise-exposed workers were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 13 publications
2
56
2
3
Order By: Relevance
“…Recently, Ariyoshi (2007) reported that the rate of wearing earplugs was 57% among noise-exposed workers 3) . Similar findings are also reported in other countries 4,5) . With regard to the proper use, Ito et al (1994) reported that in many cases earplugs were improperly used 6) .…”
supporting
confidence: 92%
“…Recently, Ariyoshi (2007) reported that the rate of wearing earplugs was 57% among noise-exposed workers 3) . Similar findings are also reported in other countries 4,5) . With regard to the proper use, Ito et al (1994) reported that in many cases earplugs were improperly used 6) .…”
supporting
confidence: 92%
“…Providing and disseminating education programs to prevent hearing loss nationally should help increase hearing-protection strategies during occupational and recreational activities [23][24][25]. Consistent implementation of hearing protective behaviors by large numbers of individuals in the United States would help reduce the prevalence and severity of hearing loss and tinnitus over time [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Lusk and colleagues (Lusk et al, 1999b) found that a single one hour training increased HPD use significantly (from 44 to 53% of time) 10-12 months post-training. Dineen and colleagues (Dineen et al, 1998) found that HPD use increased significantly (from 23% to 35%) four months post-training.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 97%